Non-ST Elevation Acute Coronary Syndrome (NSTEACS) as Hypertension-Mediated Organ Damage (HMOD) in Hypertensive Emergencies - Karina Puspaseruni; Edmond Da Rizka; Wisnu Sakulat (Cermin Dunia Kedokteran, 2023)
Hypertensive emergencies are characterized by severe increases in blood pressure with evidence of hypertension-mediated organ damage (HMOD) and are associated with an increased risk of cardiovascular events, i.e. coronary heart disease (CHD) and mortality. Case: A 75-year-old man with typical chest pain with nausea and vomiting 1 hour before admission. Blood pressure was 200/100 mmHg, ECG showed T inversion in leads II, III, AVF, V1-V6 and prolonged QT interval, cardiomegaly on chest x-ray, and leukocytosis, hyperglycemia, and hypokalemia. The diagnoses were non-ST elevation acute coronary syndrome (NSTE-ACS), hypertensive emergency, and T2DM. Treatment in the ICCU consists of intravenous antihypertensive, antiplatelet, anticoagulant, statin, nitrate, insulin, and potassium chloride for electrolyte correction. The patient was admitted to the ICCU for further observation and management. Hipertensi emergensi ditandai dengan kenaikan tekanan darah yang sangat disertai bukti kerusakan organ yang progresif (hypertension-mediated organ damage - HMOD). Keadaan ini berkaitan dengan peningkatan risiko kejadian penyakit kardiovaskular, seperti penyakit jantung koroner bahkan kematian. Kasus: Seorang laki-laki usia 75 tahun dengan nyeri dada tipikal sejak 1 jam sebelum datang ke rumah sakit disertai mual dan muntah. Tekanan darah 200/100 mmHg, pada EKG didapatkan inversi T pada lead II, III, AVF, V1-V6, dan pemanjangan interval QT. Pada pemeriksaan X-ray dada didapatkan kardiomegali, hasil laboratorium menunjukkan leukositosis, hiperglikemi, dan hipokalemi. Pasien didiagnosis non-ST elevation acute coronary syndrome (NSTE-ACS), hipertensi emergensi, dan diabetes melitus tipe 2. Tata laksana di ICCU menggunakan anti-hipertensi intravena, anti-platelet, anti-koagulan, statin, nitrat, insulin, dan kalium klorida untuk koreksi elektrolit. Pasien dirawat di ICCU untuk observasi dan tata laksana lebih lanjut.